Organizational learning to managing change: Key player of continuous improvement in the 21st century - (:unkn) unknown (IGI Global, 2017)
Nowadays, in our fast moving business world companies have to adapt changes as fast as it is possible to gain advantages among their rivals. At this point, managerial processes become vital for every company and every sector to survive. Firms' adaptation to changing environmental conditions is one of the most important topics in every century. For that reason, companies use several techniques to adapt their processes to changing conditions for gaining advantages in their market. Organizational learning is not a new concept although its importance significantly increased nowadays. This chapter aims to present a research about effects of organizational learning on managing change. For this purpose, organizational learning as a key player of continuous improvement and its key dimensions will be drawn out through this chapter. The result of this chapter will be a set of tools which describe approaches for implementing learning management to get efficient change management. © 2017 by IGI Global. All rights reserved.